1992
DOI: 10.1016/s0022-5347(17)37057-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Problems in Multicentric Renal Angiomyolipoma

Abstract: Multicentric renal angiomyolipoma is a rare form of benign tumor. However, its effective incidence as evaluated in autopsy studies may be as high as 8%. There are 2 main types of renal angiomyolipoma, that is isolated forms and those associated with other diseases, such as phakomatosis, polycystic kidneys and fibromuscular dysplasia. The tumor may also display malignant behavior with local invasiveness and regional lymph node involvement. However, the clinical course is benign and multicentricity is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Multifocality and regional lymph node involvement can occur and this is considered to represent a multifocal growth pattern rather than metastasis. 17,18 Three cases of sarcoma developing in sporadic angiomyolipoma have been reported, although a similar event has not been described in tuberous sclerosis patients. [19][20][21] Angiomyolipoma frequently shows loss of heterozygosity of variable portions of the TSC2 gene locus in both sporadic and tuberous sclerosis-associated tumors.…”
Section: Kidneymentioning
confidence: 99%
“…Multifocality and regional lymph node involvement can occur and this is considered to represent a multifocal growth pattern rather than metastasis. 17,18 Three cases of sarcoma developing in sporadic angiomyolipoma have been reported, although a similar event has not been described in tuberous sclerosis patients. [19][20][21] Angiomyolipoma frequently shows loss of heterozygosity of variable portions of the TSC2 gene locus in both sporadic and tuberous sclerosis-associated tumors.…”
Section: Kidneymentioning
confidence: 99%
“…It occurs more commonly in the isolated form and, rarely, as part of the tuberous sclerosis (TBS) complex. The isolated form is usually small and asymptomatic and is found predominantly in women in the 4th to 7th decades of life; the combined form is encountered in 40–80% of the patients with TBS and appears as multiple bilateral tumors [2]. Though hamartomas in adults usually do not have growth potential, studies have shown that AMLs may grow and compress surrounding tissue [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…They occur commonly as an isolated form and less often in association with tuberous sclerosis [2]. Patients with tuberous sclerosis are more likely to have bilateral disease, are more symptomatic and require surgery more frequently [3].…”
Section: Commentmentioning
confidence: 99%